1992
DOI: 10.2514/3.11219
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection in elastic structures using vibratory residual forces and weighted sensitivity

Abstract: A methodology is presented for detecting structural damage in elastic structures by nondestructive means. Measured modal test data along with a correlated analytical structural model are used to locate potentially damaged regions using residual modal force vectors and to conduct a weighted sensitivity analysis to assess the extent of mass and/or stiffness variations, where damage is characterized as a stiffness reduction. The current approach is unique among other approaches in that it accounts for 1) variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(46 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…The Hemez/Alvin algorithm [Hemez and Farhat (1995), Alvin (1996)] computes the sensitivities at the elemental level, then assembles them to produce the global sensitivity matrices. The Ricles/Kosmatka algorithm [Ricles and Kosmatka (1992)] computes a "hybrid" sensitivity matrix using both analytical and experimental sensitivities. …”
Section: Finite Element Model Refinementmentioning
confidence: 99%
“…The Hemez/Alvin algorithm [Hemez and Farhat (1995), Alvin (1996)] computes the sensitivities at the elemental level, then assembles them to produce the global sensitivity matrices. The Ricles/Kosmatka algorithm [Ricles and Kosmatka (1992)] computes a "hybrid" sensitivity matrix using both analytical and experimental sensitivities. …”
Section: Finite Element Model Refinementmentioning
confidence: 99%
“…Based on a concept similar to Ricles and Kosmatka [34] in their study on crack identi"cation in structures, a modi"ed estimate of the system sti!ness derivative has been constructed as given below…”
Section: Estimation Of Sensitivity Matrixmentioning
confidence: 99%
“…Using these methods, many research studies on the crack identi"cation are also reported using residual modal force as an updating parameter. A few examples are the research studies by Chen et al [32], Haug et al [33], Ricles et al [34], Farhat et al [35] and Hemez et al [36].…”
Section: Introductionmentioning
confidence: 99%
“…This method is based on the fact that structural damages usually cause decrease in the structural sti ness, which produces changes in the vibration characteristics (notably frequencies, mode shapes and damping) of the structure. The vibration data used for damage detection are such types as frequency response function [2], natural frequency [3][4][5], mode shape [6][7][8], mode shape curvature [9], modal exibility [10; 11], and modal strain energy [12], etc. Early damage detection methods use natural frequency changes as damage indicator.…”
Section: Introductionmentioning
confidence: 99%